Graf želja in poklicev - orodje za podporo procesu poklicnega usmerjanja - Molan, Marija (Delo in varnost, 2009)
High degree of aversion to the performed work amog Slovenian employee identify poor procedures of profesional counselling activities in our schools. The research in composed from two parts. In the first part 170 children from the central part of Slovenia were participated. In the second part 155 children from Koroška region were participated. On the basis of implemented, for this purpose developed tools for identification of professional secisions, the model for vocational counselling was developed. Developed model based on the graph thery in able to be used in the process of vocational counselling in the elementary school. The graph of desires, interests, impact factors and final decision, describes the whole process. Graph identifies the most important influent factors and relations between graph elements. The graph of professional decisions, desires and professions, is a tool for clear identification of impact factors. It reflects the influence of real situation and possibilities of getting the job on the professional decision.
Keywords: poklici; poklicno usmerjanje; poklicno svetovanje; interesi; otroci; child; zadovoljstvo; raziskave; Slovenia; Slovenija